Extremely Large Magnetoresistance at Low Magnetic Field by Coupling the Nonlinear Transport Effect and the Anomalous Hall Effect. Issue 14 (9th February 2016) - Luo, Zhaochu; Xiong, Chengyue; Zhang, Xu; Guo, Zhen‐Gang; Cai, Jianwang; Zhang, Xiaozhong
Abstract : The anomalous Hall effect of a magnetic material is coupled to the nonlinear transport effect of a semiconductor material in a simple structure to achieve a large geometric magnetoresistance (MR) based on a diode‐assisted mechanism. An extremely large MR (>10 4 %) at low magnetic fields (1 mT) is observed at room temperature. This MR device shows potential for use as a logic gate for the four basic Boolean logic operations.